Test of ?-Amylase Inhibition Activity in Ethanol Extract of Fennel Leaves (Foeniculum vulgare Mill.) Using Elisa Reader - Dwi Bagus Pambudi; Nuniek Nizmah Fajriyah; Retno Aulia Maharisti (Urecol Journal. Part C: Health Sciences, 2021)
Fennel has been cultivated in Indonesia as a spice and medicinal plant. Fennel can produce fennel oil, which is the result of distillation from dry and ripe fennel fruit powder, while fennel leaves are mainly cooked to make vegetables. The ?-amylase enzyme plays an important role in the breakdown of oligosaccharides and disaccharides into monosaccharides so that they are ready for absorption. Inhibition of the ?-amylase enzyme can delay and prolong the digestion time of carbohydrates, causing a decrease in the rate of glucose absorption and preventing an increase in postpandrial plasma glucose levels. Therefore, this study aims to investigate the ethanol extract of fennel leaves (Foeniculum vulgare Mill.) Against the inhibitory activity of the ?-amylase enzyme using Elisa Reader. The experimental research method was applied to test the ethanol extract of secondary metabolite compounds from fennel leaves against the inhibition of ?-amylase enzyme activity. The results showed that the IC50 value in the fennel leaf extract was 1.432 ?g/mL while the IC50 acarbose as a comparison was 3.340 ?g/mL. In conclusion, the ethanol extract of fennel leaves can be used to reduce blood sugar levels.